Agrifood supply chain network design under sustainable development policies : Conception de réseaux de chaînes logistique agroalimentaires dans le cadre de politiques de développement durable (2021)
This work addresses the research problem of quantitative support for decision-making in sustainable supply chain network design (SSCND). We first identify the common key indicators utilized to assess sustainability in supply chain design applications. We propose both (i) a single-objective and (ii) a multi- objective modeling approaches to deal with environmental and social criteria to the design of a supply chain network from a company perspective. Considering a broader perspective of sustainability in supply chains, the unit of analysis is extended from a company perspective to consider a wide-industry perspective for the sector. We specifically consider the effects of policy application on encompassing the sector towards sustainable development and its impacts in the supply network structure.